Residues with varying decomposability interact differently with seed or root exudate compounds to affect the biophysical behaviour of soil - Oleghe, E.; Naveed, M.; Baggs, E.M.; Hallett, P.D. (Geoderma, 2019)
Plants have a large impact on the physical behaviour of soil, partly due to seed and root exudates that alter mineral:organic matter associations. In this study we explored how the decomposability of residues in soil interacts with seed or root exudate compounds to influence microbial respiration, mechanical behaviour and hydrological properties. Sandy loam and clay loam soils were amended at a rate of 40 t ha−1 with ground green barley (7.13 mg C g−1), barley straw (7.26 mg C g−1) or poultry manure (5.22 mg C g−1), and either chia seed exudate at 1.84 mg C g−1 soil or root exudate compounds at 14.4 mg C g−1 soil. On cores packed to 1.3 g cm−3, uniaxial compression, penetration resistance, water sorptivity, water retention and porosity were measured at time 0, after 14 days of incubation at 20 °C, and then after subjecting incubated soils to three cycles of wetting and drying to simulate weathering. These time increments and weathering were intended to simulate a newly germinated seed or tip of a root, through to a more mature system. Application of seed and root exudate increased carbon dioxide (CO2) emissions from 0.31 ± 0.01 to 15.11 ± 0.71 μg C-CO2 g soil−1 h−1 for the sandy loam soil and from 0.171 ± 0.01 to 10.56 ± 0.78 C-CO2 g soil−1 h−1 for the clay loam soil. There were large changes in soil physical properties caused by seed or root exudate amendment coupled with residues, their decomposition and weathering. After incubation and weathering, soils with added seed or root exudates and their interactions with organic residues were more mechanically stable, as measured by penetration resistance (22 to 58% increase) and compression index (25 to 43% decrease) compared to soils amended only with organic residue. Water sorptivity and porosity diminished with the addition of the exudate. Exudates in combination with organic residues better protected soils against structural destabilization by increasing particle cementation, and decreasing rapid wetting and porosity. •Organic residue impact on soil physical behaviour enhanced by plant exudates.•Particle bonding and hydrophobicity driving changes.•Sandy loam soil was more responsive than clay loam soil.•Weathering and microbial decomposition drive temporal shifts.